Getting on board: Organizational socialization and the contribution of social capital. (March 2013) - Korte, Russell; Lin, Shumin
When starting a new job, newcomers strive to learn the tasks and expectations of their work, decipher the unwritten rules or norms of the culture, and achieve membership in the organization. The literature on the socialization of newcomers in organizations typically links success to the ability of the newcomer to learn to fit in. Yet recent empirical studies identified coworkers and managers as sharing the responsibility for successful socialization. The purpose of this study was to investigate the orientation and socialization processes (also known as onboarding) from the broader perspective of social capital. The concept of social capital generally describes the value and resources of social relations and network ties afforded to members of social networks or groups. Through a set of in-depth interviews with newly hired engineers in a large manufacturing organization, newcomers reported how they learned about and integrated into the social networks that made up their workplace. Overall, it was the quality of the relationships newcomers formed with coworkers and managers that was the primary driver of socialization outcomes.